A Meta-Analysis of the Effects of Mental Contrasting With Implementation Intentions on Goal Attainment - Wang, Guoxia; Wang, Yi; Gai, Xiaosong (Frontiers in Psychology, 2021)
Mental contrasting with implementation intentions (MCII) is a self-regulation strategy that enhances goal attainment. This meta-analysis evaluated the efficacy of MCII for goal attainment and explored potential moderators. A total of 21 empirical studies with 24 independent effect sizes (15907 participants) were included in the analysis. Results showed that MCII to be effective for goal attainment with a small to medium effect size (g=0.336). The effect was mainly moderated by intervention style. Specifically, studies with interventions based on interactions between participants and experimenters (g=0.465) had stronger effects than studies with interventions based on interactions between participants and documents (g=0.277). The results revealed that MCII is a brief and effective strategy for goal attainment with a small to moderate effect; however, because of some publication bias, the actual effect sizes may be smaller. Due to small number of studies in this meta-analysis, additional studies are needed to determine the role of moderator variables.